Animal-Origin Prebiotics Based on Chitin: An Alternative for the Future? A Critical Review - Lopez-Santamarina, Aroa (Foods, 2020)
The human gut microbiota has been revealed in recent years as a factor that plays a decisive role in the maintenance of human health, as well as in the development of many non-communicable diseases. This microbiota can be modulated by various dietary factors, among which complex carbohydrates have a great influence. Although most complex carbohydrates included in the human diet come from vegetables, there are also options to include complex carbohydrates from non-vegetable sources, such as chitin and its derivatives. Chitin, and its derivatives such as chitosan can be obtained from non-vegetable sources, the best being insects, crustacean exoskeletons and fungi. The present review offers a broad perspective of the current knowledge surrounding the impacts of chitin and its derived polysaccharides on the human gut microbiota and the profound need for more in-depth investigations into this topic. Overall, the effects of whole insects or meal on the gut microbiota have contradictory results, possibly due to their high protein content. Better results are obtained for the case of chitin derivatives, regarding both metabolic effects and effects on the gut microbiota composition.